Mediation In Settlement of Joint Marital Property Disputes: Study At Tanjung Karang Religious Court, Lampung - Syafei, Ermi Suhasti; Djazimah, Siti (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
In general, after a divorce, there are frequent disputes relating to joint marital property. The settlement of joint marital property disputes can be carried out through a mediation process applied through litigation (court) and non-litigation (outside court). The settlement of joint marital property disputes is one of the absolute jurisdictions of Religious Courts. The number of joint marital property cases successfully mediated in Religious Courts throughout Indonesia in 2018 was 6.2%, in 2019 was 5,5%. This paper describes the factors that cause unsuccessful mediation in settling disputes over joint marital properties at Tanjung Karang Religious Court, Lampung. This empirical study with qualitative analysis and a normative juridical approach interviews mediator judges, disputants, and advocates. The research results show that the implementation of the mediation process in settlements of joint marital property disputes at Tanjung Karang Religious Court in the last four years is 15.1%, which is in the low category. Factors that influence the unsuccessfulness of mediation in joint marital property disputes at Tanjung Karang Religious Court are the absence of the parties, the disputed object, and the intervention of third parties (family, friends, and lawyers).